Solar PV Minigrid Technology: Peak Shaving Analysis in the East African Community Countries - Jeanne Paula Ihirwe; Zibiao Li; Keyuan Sun; Samuel Bimenyimana; Chen Wang; Godwin Norense Osarumwense Asemota; Aphrodis Nduwamungu; Cicilia Kemunto Mesa (International Journal of Photoenergy)
Solar PV research in East Africa has concentrated on solar home systems (SHS) in each country. However, several other fundamental advances in the solar photovoltaic (PV) industry have emerged, and the developments have seen the sector experienced significant growth and diversification of models, regulation, and financing. This paper begins with an extensive narrative on the solar PV outlook of each of the six countries studied. A solar PV minigrid was also simulated using HOMER software with a critical load of 2800.0 kWh/day in order to analyze the peak shaving capability and assess the affordability of the solar PV microgrid having commercial and industrial loads. The regional overview of the efforts was identified, followed by a description of the models, payment methods, and barriers encountered collectively. The lessons from this research suggest that there is a vast potential for solar PV micro and minigrid deployment in the region with a population of over 100 million people lacking access to electricity by the end of 2019. It shows that solar PV minigrid deployment in East Africa is still at a nascent phase. Also, minigrid developers face several challenges operating in rural areas. While solar PV minigrids remain fairly nascent in the East Africa region, the technology is gaining traction, a development that indicates budding confidence in the solar PV minigrid technology. This study identifies that (1) with large critical loads (industrial and commercial), solar PV minigrid can still contribute to affordable electricity through peak shaving, except Tanzania; (2) solar PV minigrid projects are largely dependent on donor financing, require vast financial diversity to get off the ground, and offer consistent service; (3) Governments support in the form of National electrification strategies, policies, and regulation are key ingredients for realizing the electrification of rural populations through minigrids; (4) hybrid minigrids and power demand creation have emerged as an approach that ensures sustainability or profitability for the operating solar minigrid firms. Overall, government policy and regulation, funding, and financial sustainability remain the major hurdles to minigrid uptake in the region.